Tradisi Penerjemahan Al-Qur'an ke dalam Bahasa Jawa Suatu Pendekatan Filologis - Saifuddin, Saifuddin (Lajnah Pentashihan Mushaf Al-Qur'an, 2013)
In this article , the author conducted the searching which is related to the forms of the translation of the Qur'an in the Javanese language in the period before the 20th century. This study uses the resources of the ancient manuscripts of the Qur'an which is supplemented by the translation in the Javanese language. The result of the inventory the author did is that there are at least 8 Manuscripts, both within and outside the country. Some aspects that will be reviewed from those eight manuscripts are the translation, the method used, the interconnection among the texts, as well as some issues that arise in the process of translation of the Qur'an into the Javanese language.Keywords: Ancient Manuscripts, Translations, inter-row.